Theological Theological Interpretation of Scripture - Habets, Myk 1971- (2021)
Theological Interpretation of Scripture is a discipline that is growing in popularity and usefulness. This popularity has spawned many proposals for what Theological Interpretation of Scripture is and how it should be conducted. Within these proposals two general approaches to Theological Interpretation of Scripture can be identified: the biblical and the theological. While complementary, these approaches to Theological Interpretation of Scripture differ. Observing these differences allows for mutual appreciation between the two approaches. It also provides an opportunity to clarify further what theologians are doing when they undertake a theological Theological Interpretation of Scripture. After specifying what a theological Theological Interpretation of Scripture is by employing a six-point rubric which incorporates general and special hermeneutics, the differences between approaches to Theological Interpretation of Scripture by biblical scholars and theologians will be illustrated.